Molecular analysis of enteropathogenic Escherichia coli (EPEC) isolates from healthy food-producing animals and humans with diarrhoea - Beraldo, Livia Gerbasi [UNESP]; Borges, Clarissa Araújo [UNESP]; Maluta, Renato Pariz; Cardozo, Marita Vedovelli [UNESP]; de Ávila, Fernando Antônio [UNESP] (Wiley, 2023)
Enteropathogenic Escherichia coli (EPEC) is a pathogen associated with acute diarrhoea in humans. To determine whether EPEC isolated from healthy food-producing animals possesses the same virulence gene repertoire as EPEC isolated from human with diarrhoea, we compared six typical EPEC (tEPEC) and 20 atypical EPEC (aEPEC) from humans with diarrhoea and 42 aEPEC from healthy animals (swine, sheep and buffaloes), using pulsed-field gel electrophoresis (PFGE), virulence markers, serotyping and subtyping of eae and tir genes. We found that human and animal isolates shared virulence genes, including nleB, nleE and nleF, which were associated with human diarrhoea. Serogroups and serotypes identified in isolates of food-producing animals such as O26:H11, O128:H2, O76:H7, O103, O108, O111 and O145, have previously been implicated in human disease. The subtypes eae and tir were also shared between human and animal isolates, being eae-γ1 and eae-β1 the most prevalent in both groups, while the most common tir subtypes were α and β. Despite PFGE analysis demonstrating that EPEC strains are heterogeneous and there was no prevalent clone identified, EPEC isolated from humans and food-producing animals shared some characteristics, such as virulence genes associated with human diarrhoea, indicating that food-producing animals could play a role as reservoirs for those genes.
Keywords: EPEC; foodborne disease; PFGE; public health; virulence genes